Pengembangan Lembar Kerja Siswa (LKS) Berdasarkan Identifikasi Jenis-Jenis Gastropoda di Kawasan Hutan Mangrove - Sumitro Robo; Lintal Muna; Juniartin Juniartin; Astuti Muh Amin (IAIN Ternate, 2021)
The importance of developing student worksheets (LKS) based on the results of the identification of gastropods in Indari Village is very useful for students to know the importance of the role of gastropods in our environment, therefore the student worksheets can be used to present contextual material, namely developing students' prior knowledge, and also invites students to think critically through practicum in the teaching and learning process takes place. In order for this subject to be well received by students, it is necessary to have a student worksheet (LKS) which aims to accommodate and encourage students' thinking skills and support students to be able to think for themselves, analyze themselves, and arrange the final results of student activities according to developments. student psychology. The type of research used in this research is research and development which consists of Define, Design, Develop, and Disseminate. Based on the results of research conducted in the mangrove forest area of Indari Village, it can be found as many as 15 types of gastropods with different characteristics and shapes. The total number of gastropods found was 547 individuals. The most common species found was Nerita sp with 82 individuals while the least species found was Chicereus capueinus with 7 individuals. The development of LKS teaching materials using the 4-D model is feasible based on the results of the validation carried out by material expert validators and design experts.